2020
DOI: 10.3389/fpsyg.2020.00392
|View full text |Cite
|
Sign up to set email alerts
|

Skin Color Cues to Human Health: Carotenoids, Aerobic Fitness, and Body Fat

Abstract: Colorful carotenoid ornaments are sexually selected signals of health in many species. In humans too, carotenoids could provide a perceptible cue to health as they impart an attractive yellow-orange color to skin. Increasing carotenoid pigmentation and skin yellowness is associated with increased fruit and vegetable intake, but whether other aspects of human health benefit skin color is unknown. Carotenoids, as antioxidants, help maintain oxidative balance but are expended in this role. Therefore, any health f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…These results were largely driven by male transforms being rated as more dominant, and female faces being rated as happier and less babyish. These results largely follow from the observation that quadrant I faces typically appear more "smiley" and appear to have healthy skin color (carotenoids; see, e.g., Perrett et al, 2020). These effects are further corroborated by the results from the happy transforms (see Supplementary Material 6).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…These results were largely driven by male transforms being rated as more dominant, and female faces being rated as happier and less babyish. These results largely follow from the observation that quadrant I faces typically appear more "smiley" and appear to have healthy skin color (carotenoids; see, e.g., Perrett et al, 2020). These effects are further corroborated by the results from the happy transforms (see Supplementary Material 6).…”
Section: Discussionsupporting
confidence: 68%
“…The present results confirm that in addition to facial structure, color and texture related to emotion expressions are also important cues individuals use to make decisions. Research that has examined these cues in isolation demonstrated that they impact perceptions related to attractiveness and health (Pazda et al, 2016 ; Thorstenson et al, 2017 ; Perrett et al, 2020 ) as well as gender (Russell, 2003 , 2009 ). It is certainly possible face color and texture influence impressions related to gender or health in a largely associative manner, much like how face structure has been shown to influence impressions via emotion overgeneralization (see, Heerey and Velani, 2010 ; Kocsor et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In data sets used in two previous studies, we find that for men (N = 101, 79 respectively) the effect size relating impedance measured Fat% to muscle mass was 0.75-0.85, controlling for body weight(Lei et al, 2018;Perrett, Talamas, Cairns, & Henderson, 2020).…”
mentioning
confidence: 65%
“…The demonstration was made early in the survey, which may have led to participants increasing their reported fruit and vegetable consumption. The dietary effect on skin color is not unique since other aspects of lifestyle (eg, fitness and reduced body fat) have similar impacts on skin color appearance [ 39 ].…”
Section: Discussionmentioning
confidence: 99%